2014
DOI: 10.1007/978-1-4939-1804-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Epigenetics: An Introduction

Abstract: Epigenetic and genetic alterations contribute to cancer initiation and progression. Epigenetics refers to the study of heritable changes in gene expression without alterations in DNA sequences. Epigenetic changes are reversible and include key processes of DNA methylation, chromatin modifications, nucleosome positioning, and alterations in noncoding RNA profiles. Disruptions in epigenetic processes can lead to altered gene function and cellular neoplastic transformation. Epigenetic modifications precede geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
152
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(163 citation statements)
references
References 117 publications
1
152
0
3
Order By: Relevance
“…Therefore, it is necessary to thoroughly investigate the pathogenetic mechanism of HCC and develop new targeted treatments. The majority of recent investigations into cancer etiology have identified that epigenetics serves a critical role in cancer (27,28). Alterations in epigenetic modifications regulate all DNA-based processes, including transcription, DNA repair and replication, and are considered to be early events in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to thoroughly investigate the pathogenetic mechanism of HCC and develop new targeted treatments. The majority of recent investigations into cancer etiology have identified that epigenetics serves a critical role in cancer (27,28). Alterations in epigenetic modifications regulate all DNA-based processes, including transcription, DNA repair and replication, and are considered to be early events in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, epigenetic modifications are known to precede genetic alterations in human neoplasms [57]. Therefore, we believe that the ENI plays a significant role in the initiating stages of NEPC trans-differentiation via epigenetic modification of downstream gene targets.…”
Section: The Epigenetic/non-coding Interactome and Its Implication Inmentioning
confidence: 94%
“…REST is part of the KDM1A-coREST-REST (Lysine-specific histone demethylase 1A-REST Corepressor 1-RE1-silencing transcription factor) histone modifying complex which is bound by HOTAIR, a long intergenic ncRNA that coordinates histone H3 lysine 27 methylation and lysine 4 demethylation [54]. Given that REST is commonly inactivated in NEPC and is responsible for repressing neuronal genes [55], aberrant silencing of this gene could trigger neuronal differentiation programs in trans-differentiating cells [56].Notably, epigenetic modifications are known to precede genetic alterations in human neoplasms [57]. Therefore, we believe that the ENI plays a significant role in the initiating stages of NEPC trans-differentiation via epigenetic modification of downstream gene targets.…”
mentioning
confidence: 99%
“…These evidence strongly supports the notion that epigenetic mechanisms may act as driving forces during carcinogenesis and support cancer cell survival and proliferation. Based on this notion, epigenetic regulatory enzymes are considered as important targets for cancer therapy 3 . Several drugs targeting DNA methylation and histone acetylation have been approved for cancer treatment in clinic 3 .…”
Section: Epigenetic Dysregulation In Cancermentioning
confidence: 99%
“…Based on this notion, epigenetic regulatory enzymes are considered as important targets for cancer therapy 3 . Several drugs targeting DNA methylation and histone acetylation have been approved for cancer treatment in clinic 3 . DNMT inhibitors, such as the cytidine analogues 5-azacytidine and 5-aza-2'deoxycytidine, can be incorporated into the daughter strands of DNA during DNA replication, which leads to DNA demethylation because This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Epigenetic Dysregulation In Cancermentioning
confidence: 99%